2011
DOI: 10.1021/ac200076c
|View full text |Cite
|
Sign up to set email alerts
|

Protein Sensing and Cell Discrimination Using a Sensor Array Based on Nanomaterial-Assisted Chemiluminescence

Abstract: Cross-reactive sensor arrays, known as "chemical noses", offer an alternative to time-consuming analytical methods. Here, we report a sensor array based on nanomaterial-assisted chemiluminescence (CL) for protein sensing and cell discrimination. We have found that the CL efficiencies are improved to varied degrees for a given protein or cell line on catalytic nanomaterials. Distinct CL response patterns as "fingerprints" can be obtained on the array and then identified through linear discriminant analysis (LDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 24 publications
3
75
0
Order By: Relevance
“…Although the molecular recognition of solution analytes using a sensor array is inherently challenging, due to potential interference from the very high concentration of water [147], we expect that the present CTL-based sensor array could be extended to discrimination of samples in solution, since it is found that saccharides, amino acids, and steroid pharmaceuticals can produce CL emission on the surface of many nanomaterials [116,117,124,[126][127].…”
Section: Identification Of Organic Compounds In Aqueous Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the molecular recognition of solution analytes using a sensor array is inherently challenging, due to potential interference from the very high concentration of water [147], we expect that the present CTL-based sensor array could be extended to discrimination of samples in solution, since it is found that saccharides, amino acids, and steroid pharmaceuticals can produce CL emission on the surface of many nanomaterials [116,117,124,[126][127].…”
Section: Identification Of Organic Compounds In Aqueous Solutionsmentioning
confidence: 99%
“…As the phenomenon of CL is also observed when organics or biological substances are thermally oxidized and catalysis-amplified reactions also significantly increase thermochemiluminescence (TCL) intensity, Zhang's group applied a similar TCL-sensor array to study protein sensing and cell discrimination [126]. On the basis of distinct CL patterns generated by the catalytic nanomaterial array, 12 kinds of protein at three concentrations (5 μg·mL -1 , 10 μg·mL -1 and 20 μg·mL -1 ), and 12 types of human cell line from normal, cancerous, and metastatic were successfully sensed and discriminated.…”
Section: Recognition Of Small Biological Moleculesmentioning
confidence: 99%
“…Zhang's group [81,82] has reported a series of nanomaterial-based optical chemosensor arrays to recognize volatile components/samples such as alcohols and flavors, organic acids and amino acids [83], proteins and cell lines [84], and sweeteners [85]. In addition, this type of sensor arrays was used to establish a new and rapid approach for evaluating and screening catalysts during the oxidation of CO [86,87].…”
Section: Sensorsmentioning
confidence: 99%
“…For the high sensitivity, excellent selectivity and simplicity, the fluorescence detection is applicable for determining the concentration levels of formaldehyde rapidly and accurately [19][20][21][22][23][24]. However, the fluorimetric derivatization processes of formaldehyde generally need strong acid, high temperature or long time [5,25,26].…”
Section: Introductionmentioning
confidence: 99%